SAT0184 Ct Scan Confirms Presence of Erosion in Systemic Lupus Erythematosous and Primary Sjogren's Syndrome as Well as Healthy Control, with Different Characteristics as Compared to Rheumatoid Arthritis: an Observational Study of 90 Subjects. (10th June 2014) - Gandjbakhch, F.; Foltz, V.; Renoux, J.; Cozic, N.; Costedoat, N.; Sene, D.; Mercy, G.; Amoura, Z.; Piette, J.-C.; Morel, N.; Bourgeois, P.; Fautrel, B.
Abstract : Background: Recent studies showed that MRI erosion may occur in Systemic Lupus Erythematosous (SLE) and primary Sjogren's syndrome (pSS) 12 . TDM is considered as gold standard for bone evaluation. Objectives: To describe TDM characteristics for the detection of erosion in patients with SLE and pSS without association with rheumatoid arthritis (RA) compared to "positive control", i.e. RA and "negative control" (sex/age-matched healthy controls). Methods: pSS, SLE, RA patients and HC were prospectively included from 2 university departments (rheumatology and internal medicine) between 2009 and 2011. Inclusion criteria were: 1. For lupus and primary SS: disease duration >2 years, no association with RA (i.e. no arthritis, no ACPA, normal X rays of hand and feet). 2. For healthy controls (HC): no history of tender or swollen joint or rheumatic disease. 3. For RA: established disease with duration >2 years. CT scan and MRI of MCP2 to 5 and wrist of the dominant hand was performed in coronal and axial plans. Adaptation of the OMERACT definition for erosion was used in order to differenciate physiological cortical break, i.e. vascular foramen and erosion due to destructive disease. CT scan and MRI were evaluated according to RAMRIS by 2 independent readers, blindly to clinical and radiographic data. Results: 90 subjects were included prospectively in the study: 19 primary SS, 21 Lupus, 32 RA and 20 HC.Patients characteristics were previously described 1 . 83% of RA patients were erosive on X-rays. All SLE/pSS patients had normal Xrays of hand and feet (inclusion criteria). Good correlation was observed between MRI and CT scans (Pearson coefficient 0.77, p<0.0001; intraclass correlation coefficient (icc): 0.74). On CT scan, almost all patients and HC had at least one cortical break seen in 2 plans without statistical difference between the groups. Frequencies of patients having at least one erosion and mean number of erosions were statistically different between RA and SLE/pSS, while no statistical difference was seen between SLE/pSS and HC. RAMRISerosion was higher in RA and statistically different from non-RA patients (Table). Erosions were most frequently observed in wrists with higher frequency in RA. Conclusions: CT scan of hands/wrist correlates well with MRI and confirms presence of erosions different from vascular foramen in SLE/pSS as well as in HC. Erosions in SLE/pSS are similar with HC and differ from erosions seen in RA. References: Gandjbakhch et al. EULAR 2013-OP0175. Boutry et al. Radiology. 2005 Aug;236(2):593-600. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5655